Comparative study of the UV spectra of various raw materials OF Urtica dioica L. - E. A. Balagozyan; V. A. Kurkin; O. E. Pravdivtseva (Фармация и фармакология (Пятигорск))
Stinging nettle (Urtica dioica L.) is one of the famous and popular medicinal plants. In Russia the herbal materials are nettle’s leaves which have haemostatic effect. At the same time abroad the rhizomes and roots of nettle are the source of drugs with antitumor activity. The chemical composition of the rhizomes and roots of nettle is quite complicated and is represented by substances such as polysaccharides, lectins, sterols etc. The aim of the present study is the comparative phytochemical research of various parts of raw nettle by spectrophotometry. The study of extracts from various raw materials of nettle has shown, that the presence of flavonoids is peculiar for leaves, flowers and fruits. Sterols dominate in the rhizomes and roots of nettle. It was also noted that the UV-spectra of extracts of female inflorescences and fruits nettle have the same absorption maxima.